The Pressing Issue of Micro- and Nanoplastic Contamination: Profiling the Reproductive Alterations Mediated by Oxidative Stress - Maria Carmela Ferrante; Anna Monnolo; Filomena Del Piano; Giuseppina Mattace Raso; Rosaria Meli (MDPI AG, 2022)
Micro- and nanoplastics (MPs/NPs) are among the most widely distributed pollutants in the environment. It has been suggested that exposure to MPs/NPs can trigger toxicity pathways among which inflammation and oxidative stress (OS) play a pivotal role. Once absorbed, MPs/NPs may act locally or access the bloodstream and, following the translocation process, reach several organs and tissues, including the gonads. Notably, MPs/NPs can bioaccumulate in human and murine placenta, opening new scenarios for toxicological evaluations. We review recent studies on the effects of MPs/NPs on the reproductive health in aquatic and terrestrial organisms of both sexes, focusing on the role of OS and the antioxidant defence system failure as the main underlying mechanisms. Alterations in gametogenesis, embryonic and offspring development, and survival have been shown in most studies and often related to a broken redox balance. All these detrimental effects are inversely related to particle size, whereas they are closely linked to shape, plastic polymer type, superficial functionalization, concentration, and time of exposure. To date, the studies provide insights into the health impacts, but no conclusions can be drawn for reproduction toxicity. The main implication of the few studies on antioxidant substances reveals their potential role in mitigating MP-induced toxic effects.